Numerical Solution of the Non-Linear Singular Systems from Fluid Dynamics Using Leapfrog Method - Vijayarakavan, M.; Amirthalingam, V. (International Journal of Engineering and Technology, 2018)
In this Research article, the new proposed technique for examination of the singular non-linear problem from Fluid dynamics utilizing Leapfrog Method is exhibited. To represent the adequacy of the Leapfrog Method, the different cases in singular non-linear system from Fluid dynamics have been considered and contrasted and the Single Term Haar Wavelet Series and results are observed to be extremely precise. The arrangements of the non-singular particular problems from Fluid dynamics are introduced in the tables. The proposed method can be effortlessly utilized in an advanced Computer.Â Â